2001
DOI: 10.1038/35051606
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of the apoptosis effector Apaf-1 in malignant melanoma

Abstract: Metastatic melanoma is a deadly cancer that fails to respond to conventional chemotherapy and is poorly understood at the molecular level. p53 mutations often occur in aggressive and chemoresistant cancers but are rarely observed in melanoma. Here we show that metastatic melanomas often lose Apaf-1, a cell-death effector that acts with cytochrome c and caspase-9 to mediate p53-dependent apoptosis. Loss of Apaf-1 expression is accompanied by allelic loss in metastatic melanomas, but can be recovered in melanoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

36
687
4
12

Year Published

2001
2001
2009
2009

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 881 publications
(739 citation statements)
references
References 28 publications
36
687
4
12
Order By: Relevance
“…Kondo et al [20] have reported that 5Aza-dC dramatically decreases histone H3 Lys-9 methylation, slightly increases Lys-9 acetylation, and moderately increases histone H3 Lys-4 methylation and reactivated gene expression. These findings could explain the previously reported 5Aza-dC induced activation of the un-methylated gene [21,22] and could also explain the maspin activation in our results.…”
Section: Discussionsupporting
confidence: 90%
“…Kondo et al [20] have reported that 5Aza-dC dramatically decreases histone H3 Lys-9 methylation, slightly increases Lys-9 acetylation, and moderately increases histone H3 Lys-4 methylation and reactivated gene expression. These findings could explain the previously reported 5Aza-dC induced activation of the un-methylated gene [21,22] and could also explain the maspin activation in our results.…”
Section: Discussionsupporting
confidence: 90%
“…Mutations in the genes coding for transcription factors p53 (Vogelstein et al, 2000), the retinoblastoma protein (Sherr and McCormick, 2002), BRCA1, BRCA2 (Venkitaraman, 2002) and the Interferon (IFN)-gene regulatory factor-1 (Willman et al, 1993;Tanaka et al, 1996) yield functionally-inactive proteins, which fail to inhibit cell growth and thus have been linked to the development of tumors. In addition to these transcription factors, mutations or loss of expression of cellular genes coding for the apoptotic machinery also promotes tumor cell growth (Lowe et al, 1994;Knudson et al, 1995;Soengas et al, 2001;Pingoud-Meier et al, 2003;Stupack et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Once established, this state is mitotically heritable and contributes to the stable silencing of tumor suppressor and other genes. Several proapoptotic genes succumb to epigenetic silencing in human tumors, including CASP8, the TNFrelated apoptosis-inducing ligand (TRAIL) receptors TNFRSF10A and TNFRSF10B, the caspase-9 adaptor APAF1 and the death-associated protein kinase, DAPK (Kissel et al, 1997;Teitz et al, 2000;Soengas et al, 2001;van Noesel et al, 2002;Furukawa et al, 2005;Horak et al, 2005), suggesting that acquired epigenetic alterations also contribute to apoptotic resistance during tumor progression.…”
Section: Introductionmentioning
confidence: 99%